2020
DOI: 10.1038/s41598-020-58924-5
|View full text |Cite
|
Sign up to set email alerts
|

Efficient extraction of cucurbitacins from Diplocyclos palmatus (L.) C. Jeffrey: Optimization using response surface methodology, extraction methods and study of some important bioactivities

Abstract: Diplocyclos palmatus (L.) C. Jeffrey is an important medicinal plant used in several reproductive medicines. It serves as a wide source of tetracyclic triterpens called cucurbitacins. Response surface methodology (RSM) with Box-Behnken design (BBD) was studied to optimize the production of cucurbitacins. RSM put forth the ideal conditions such as 1:30 SS ratio (g/mL), 80 rpm (mixing extraction speed), 150 µm mean particle size, 30 min extraction time and 50 °C using chloroform in continuous shaking extraction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 48 publications
1
13
0
Order By: Relevance
“…An increase in the volume up to 240 μL led to a considerable rise in the extraction efficiency, which can be attributed to more interaction of the solvent with the dye. The extraction decreases with increasing the eluent volume up to 300 μL due to the volume dilution [31–33] …”
Section: Resultsmentioning
confidence: 99%
“…An increase in the volume up to 240 μL led to a considerable rise in the extraction efficiency, which can be attributed to more interaction of the solvent with the dye. The extraction decreases with increasing the eluent volume up to 300 μL due to the volume dilution [31–33] …”
Section: Resultsmentioning
confidence: 99%
“…As a comprehensive mathematical and statistical method, RSM has been applied to optimize multiple factors [30][31][32], and BBD is a traditional method that is used in the experimental design [33,34]. In the article, the factors of limewater concentration, processing time and solvent volume were listed to optimize the technology of LCSS based on BBD.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphomolybdenum reduction assay: Antioxidant activity was studied by using phosphomolybdenum reduction assay [11] . An aliquot of extract was mixed with 1 ml reagent (0.6 M sulfuric acid, 28 mM sodium phosphate and 4 mM ammonium molybdate).…”
Section: Ferric Reducing Antioxidant Property Assay (Frap)mentioning
confidence: 99%
“…Nagarani et al [9] revealed the efficiency of Momordica species in the treatment of DM and AD based on α-amylase, α-glucosidase and acetylcholine esterase inhibitory activities. In addition, antidiabetic and anti-Alzheimer potential of Lagenaria siceraria and Diplocyclos palmatus have been also reported [10,11] .…”
mentioning
confidence: 97%